2018
DOI: 10.3386/w24958
|View full text |Cite
|
Sign up to set email alerts
|

Top of the Class: The Importance of Ordinal Rank

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 80 publications
2
33
0
Order By: Relevance
“…18 These effects are in line with the non-experimental results reported by Murphy and Weinhardt (2016). Besides effects on student performance within subjects, the results from this English study suggest that, conditional on ability, a high-rank position in primary school in a particular subject has long-term effects on test scores and subject choice, particularly for boys.…”
Section: Relative (Vs Absolute) Gradingsupporting
confidence: 80%
“…18 These effects are in line with the non-experimental results reported by Murphy and Weinhardt (2016). Besides effects on student performance within subjects, the results from this English study suggest that, conditional on ability, a high-rank position in primary school in a particular subject has long-term effects on test scores and subject choice, particularly for boys.…”
Section: Relative (Vs Absolute) Gradingsupporting
confidence: 80%
“…Murphy & Weinhardt (2013)). This can explain why weaker students do not improve in the boarding school, as they lose many ranks when they join.…”
Section: Ready For Boarding?mentioning
confidence: 99%
“…Though this interpretation is somewhat speculative, we review other potential mechanisms, and we argue that they cannot fully account for all of our findings. For instance, recent research has shown that higher within-class ordinal position has a positive effect on academic performance (see Murphy & Weinhardt (2013)). This can explain why weaker students do not improve in the boarding school, as they lose many ranks when they join.…”
Section: Introductionmentioning
confidence: 99%
“…We follow Murphy & Weinhardt (2014) and employ a speci cation with schoolspeci c grade xed e ects. This strategy eliminates di erences in grade means of observable and unobservable characteristics; identi cation comes from di erences in the dispersion of the ability distribution across grades within a school.…”
Section: Identification and Estimation Strategymentioning
confidence: 99%
“…A large literature in psychology focuses on a student's academic self-concept, showing that students with a higher ordinal rank have a higher perceived ability in various school subjects (Marsh, 1987;Marsh et al, 2007). The rst rigorous causal estimate of ordinal rank on educational performance is provided by Murphy & Weinhardt (2014), who use administrative school data from the UK, and nd a strong positive impact of ordinal rank in primary school on test scores in secondary school. Our paper uses a very similar research design, but departs from their study in two important dimensions.…”
Section: Introductionmentioning
confidence: 99%